The Obligation of The State to Realize Sharia-Compliant Certainty in Islamic Banking Financing - Hamidah, Siti; Saputra, Gusti Wimba (Batulis Civil Law Review, 2024)
Introduction: Islamic banking is growing significantly and rapidly. The state needs its presence not only related to providing the right to freedom of religion but also ensuring that its implementation is following the provisions of sharia. Islamic banks have received a lot of criticism due to the existence of prohibited elements specifically in financing. Therefore, a supervision system for sharia compliance is needed.Purposes of the Research:  This paper analyzes the basis and form of state obligations and their manifestation in ensuring compliance with Sharia principles in Islamic banking financing contracts in Indonesia. Because the State Financial Services Authority as the party with the authority in supervision has not reached the conformity of Sharia principles in the agreement as a private aspect.Methods of the Research: The problem analysis methodology involves legal research with a philosophical approach. The Statute Approach is conducted by reviewing applicable legal regulations, while the Analytical Approach involves analyzing legal principles and understanding through the examination of legal materials using techniques such as grammatical, teleological, and systematic interpretation.Results of the Research: The state is responsible for ensuring Sharia compliance in Islamic banking financing stems from the basic principles of Pancasila and the Constitution, as reflected in various laws, regulations, and fatwas of the National Sharia Council. These regulations serve as guidelines for sharia-compliant financing. However, legal certainty is needed in supervision and sanctions in implementing Sharia compliance.